(untitled) (Revista Argentina de Cirugía, 2026)
Background: Health systems worldwide have been affected in their fight against COVID-19, generating negative effects on both healthcare activity and training of residents. Cancellation of elective surgeries, less participation of residents in the operating room and other structural changes in the hospitals resulted in an educational gap in the training of residents in surgery. Material and methods: We conducted an observational and cross-sectional study. A 20-questiononline su rvey was conducted among residents in surgery from Argentina. A database was created for statistical analysis of categorical and continuous variables. Results: The survey was responded by 100 residents in surgery; most of them belonged to public institutions. There was a 63% decrease in the number of surgeries in which the residents participated during the pandemic. Seventy-seven percent used virtual platforms to mitigate the impact on academic training and 57% count with surgical simulation programs in their hospitals. Most of them experienced negative consequences on their surgical skills and training during the pandemic, but there were differences identified between the group with and without surgical simulation programs. Conclusion: The availability of surgical simulation programs and the use of virtual platforms as an academic training tool could solve the educational gap generated by the COVID-19 pandemic and enhance the learning of surgical skills under normal conditions.